Inovasi IPTEK dan Mutu Pendidikan Perguruan Tinggi yang Modern, Kompeten, dan Berintegritas: Science and Technology Innovation and the Quality of Modern, Competent, and Integrity Higher Education - Gulo, Elisari (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Science and technology innovation is a solution that needs to be designed and implemented that become competitive in developing countries by having the ability to innovate to become a strong, independent, respected country, and to produce quality human resources for the common good. In this technological system, it plays an important role in producing innovation, especially in the field of science and technology and the quality of higher education. As time goes by, the rapid development and technological revolution raises very serious challenges in every university in the development of global and regional times that affect the social life of the nation and state, for that we need a strategy to foster the spirit of the younger generation in the development of the modern word of science and technology, competent, and with integrity. Realizing an Indonesia that is empowered at the global level requires analysis, productivity evaluation, improving the quality of education and designing science and technology policies and innovations that are comprehensive in an integrated, open, and high-quality manner.